Male and Female EFL Students' Language Learning Strategies - Juniati Dika; Muh. Basri Jafar; Murni Mahmud (Har Press Indonesia, 2021)
The study's objectives were to (1) identify language learning strategies used by students in EFL classrooms and (2) distinguish between male and female language learning strategies. The research was carried out at STKIP YPUP Makassar in July 2021. The population of this study was 6th semester students, who comprised the sample class 6.1. Questionnaires were used as the instrument. In this study, the descriptive research method was used to describe the language learning strategies of students in an EFL classroom. The SILL questionnaire (Strategy Inventory for Language Learning) version7.0 was used to collect data. The collected data were analyzed by calculating the students' responses to the questionnaire and categorizing them to a specific level of SILL profile result. This study discovered that (1) the most frequently used language learning strategies by students are social strategies, with a mean score of 3.91, cognitive strategies, with a mean score of 3.79, compensation and affective strategies, with a mean score of 3.68, metacognitive strategies, with a mean score of 3.65, and memory strategies, with a mean score of 3.65. Indirect strategies included metacognitive, affective, and social strategies. The results revealed that direct strategies were frequently used, as evidenced by its mean score, in social strategy. It can be concluded that students prefer indirect strategies to direct strategies when learning a language. (2) There is no statistically significant difference between men and women in their use of language learning strategies. Male students use cognitive strategies more frequently than female students, despite the lack of a statistically significant difference, while female students use social strategies more frequently than male students. Students used a variety of language learning strategies, according to the findings of this study.